PREVALENCE, RISK FACTORS, AND CLINICAL OUTCOMES ASSOCIATED WITH CARBAPENEM-RESISTANT GRAM-NEGATIVE BACILLI INFECTIONS IN A TERTIARY CARE HOSPITAL: A PROSPECTIVE CROSS-SECTIONAL STUDY - Dr. Anju Gupta; Dr. Ankur Mitruka (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Carbapenem resistance among Gram-negative bacilli represents a critical global health challenge. This study aimed to determine the prevalence of carbapenem resistance, identify associated risk factors, and evaluate clinical outcomes in a tertiary care setting in India. Methods: A prospective cross-sectional study was conducted over six months in Department of Microbiology at Vyas Medical College & Hospital, Jodhpur, a tertiary care teaching hospital. Consecutive non-duplicate Gram-negative bacilli isolated from clinical specimens underwent antimicrobial susceptibility testing according to CLSI guidelines. Demographic and clinical data were collected using standardized forms. Chi-square tests and logistic regression were performed to identify risk factors, with p<0.05 considered statistically significant. Results: Among 330 Gram-negative isolates, 48.5% exhibited carbapenem resistance, with the highest rates in Acinetobacter baumannii (85.7%), followed by Pseudomonas aeruginosa (60.7%), Klebsiella pneumoniae (58.6%), and Escherichia coli (27.1%). Resistance rates varied across clinical settings: intensive care units (66.9%), surgical wards (41.2%), medical wards (39.1%), and outpatient departments (28.3%). Multivariate analysis identified prior carbapenem use (adjusted OR: 3.95, 95% CI: 2.41-6.48), ICU stay >7 days (adjusted OR: 3.22, 95% CI: 1.96-5.29), and mechanical ventilation (adjusted OR: 2.86, 95% CI: 1.74-4.71) as independent risk factors. Patients with carbapenem-resistant infections experienced higher mortality (26.9% vs. 11.2%, p<0.001), longer hospital stays (18.7 vs. 11.3 days, p<0.001), and lower clinical cure rates (57.5% vs. 80.0%, p<0.001) compared to those with susceptible infections. Conclusion: The high prevalence of carbapenem resistance, particularly in ICUs, underscores the urgent need for antimicrobial stewardship, enhanced infection control practices, and routine surveillance. The significant association with poorer clinical outcomes highlights the importance of early detection and appropriate management strategies to mitigate the impact of these challenging infections.